Interpreting Urban Spaces in Italian Cultures - Scapolo, Andrea (Spatial Imageries in Historical Perspective Ser., 2022)
Made up of both material and symbolic elements, the urban space is always dynamic and transitional; it brings together or separates the past and the present, the public and the private, the center and the periphery. The present volume focuses on the interaction between the social processes and spatial forms that shape the identity of Italian cities. Using both canonical and less well-known texts along with cultural artifacts, the essays in the volume deprovincialize the Italian city, interpreting the material and symbolic practices that have made it into a unique entity whose enduring influence extends far outside Italy.